PROXIMAL FEMUR HISTO-MORPHOLOGICAL CHANGES AMONG HIP FRACTURE IN ELDERLY PATIENTS - Akbar, Wajid; Imtiaz, Humaira; Halima, Amna; Javed, Sumaira; Naureen, Ayesha; Ali, Usman (Journal of Ayub Medical College Abbottabad, 2020)
Background: Hip fracture causes high morbidity in elderly. Decreased bone mineral density is associated with hip fracture risks. The study is conducted to identify relationship of histo-morphological changes in proximal femur in the cases of hip fractures in elderly with histo-morphological changes in proximal femur. Methods: A total of 30 elderly patients with hip fracture were studied in this case series. The study was carried out in Orthopaedic and Pathology departments at Mardan Medical Complex from May 2014 to October 2014. Specimen during surgery, were collected for histopathological study. Results: Bone biopsy of hip fracture cases revealed cortical thinning, reduced number of osteocytes, thinning and fragmentation of trabeculae. Conclusion: This study concluded that bone micro architectural changes seems to be associated with the risk of hip fracture. Keywords: Proximal femur; Histo-morphology; Hip fracture